Juridical Review Concerning the Legitimacy of Cryptocurrency in Islamic Law - Christopher Panal Lumban Gaol; Utzinger Morales; Vanella Lopez (P3M IAI Nusantara Batang Hari, 2022)
Cryptocurrency has become a significant phenomenon in the global financial world. However, within the context of Islamic law, questions regarding the validity and regulation of cryptocurrency remain a complex debate. This research aims to conduct a normative juridical analysis of cryptocurrency regulation in Islamic law, with a focus on a case study in Indonesia. The research method employed is a normative juridical approach, involving the collection and analysis of legal data from relevant sources, such as laws, regulations, and religious fatwas. This legal data is then analyzed using legal arguments and theoretical frameworks to understand and explain the legal status of cryptocurrency within Islam. This study identifies key issues that arise in the regulation of cryptocurrency in Islamic law in Indonesia, including riba (interest), gharar (uncertainty), maysir (gambling), and consumer protection. Through this normative juridical analysis, the researcher explores existing legal interpretations, relevant legal documents, and the perspectives of Islamic scholars and experts regarding the validity and permissibility of cryptocurrency. The findings of this research provide an in-depth understanding of how cryptocurrency can be categorized within the framework of Islamic law, as well as the legal implications arising from the use and trading of cryptocurrency. Additionally, this study identifies gaps and challenges in the regulation of cryptocurrency in Islamic law in Indonesia and provides recommendations for the development of more effective regulations that align with Islamic principles.